Evaluation of marginal and internal adaptation of zirconia crowns constructed from traditional and digital impressions - Loura Shawqi Marqus Jumaah; Nabeel Seryoka Hanna Martani (Erbil Dental Journal)
Background and objective: Recent advancement in restorative dentistry from impression to fabrication is toward digital workflow. There are very few studies, evaluating the internal and marginal fitness of full anatomic zirconia crowns fabricated with different impression techniques. The aim of this study was to determine whether improved technology of digital workflow results in better fitting crowns.